'Simple' surface-fire heat treatment significantly improves silcrete flake quality and flaking efficiency. (April 2020) - Pargeter, Justin; Schmidt, Patrick
Highlights: Two naturalistic flaking experiments test wood fuels and heating strategies applied to silcrete. Cores and flakes compared for utility (cutting edge/mass) and edge quality (edge angle). 'Simple' surface-fire heating significantly increases core utility and flake quality. Technological innovations efficient with low levels of technological investment. Results challenge existing behavioral models for silcrete heat treatment. Abstract: Intentional stone heat treatment is a key marker for prehistoric behavioural variability. Yet, the relationship between differences in heat-treatment strategies and variations in stone tool-making processes remains heavily debated and poorly understood. We report on two experiments testing wood fuels and heating strategies applied to silcrete nodules from 60 km south of Diepkloof Rock shelter in South Africa with early evidence for intentional silcrete heat treatment. We flaked the heated silcrete nodules to maximize miniaturized flake production. The resulting cores and flakes were compared in terms of their utility (flake cutting edge to mass) and cutting edge quality (cutting edge angles) in addition to quantifying woody residues and heat induced fracture rates. Our results show that 'simpler' surface-fire heat treatment strategies provide significant increases in miniaturized core utility and flake quality over unheated silcrete nodules. Some of these effects were obtained without more specialized knowledge than is required to maintain fires for cooking and other utilitarian purposes. Our results show that rapidly heating silcrete to modify rocks for miniaturized stone tool production is efficient at relatively low levels of technological investment.